Mitigating Climate Change and Hunger in Nigeria’s Niger Delta: Evaluating Government Policies and Strategies - Eniwotu; Victor , Clark Esekumuemu; Ayegbunan, Ikenga Francis (PERSPEKTIF, 2025)
This study explored the effectiveness of government policies and strategies in addressing climate change and hunger in Nigeria's Niger Delta region. The region, grappling with severe environmental degradation, rising temperatures, and widespread food insecurity, faces multifaceted challenges that demand targeted policy responses. The study highlights key efforts to tackle climate change, improve food production, and enhance community well-being by evaluating current government actions. The study reveals that although specific policies have made progress, such as increased funding for climate adaptation and promotion of sustainable farming, these efforts are hindered by challenges like poor implementation, inadequate infrastructure, and limited local involvement. The study emphasized the need for greater collaboration between government, local communities, and international partners to ensure the success of climate and food security initiatives. Recommendations include improving infrastructure, raising awareness and education on sustainable agricultural practices, and enhancing the capacity of local governments to carry out policies effectively. This study contributes to the existing literature by providing a thorough evaluation of Nigeria's climate change and hunger mitigation strategies in the Niger Delta, offering valuable insights to guide future policymaking and regional approaches. The findings underscore the necessity of addressing local needs and promoting community participation in creating sustainable solutions to climate change and food insecurity.